2023
DOI: 10.3389/fpsyg.2022.1072719
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of open dialogue in Germany: Efforts, challenges, and obstacles

Abstract: PurposeThe Open Dialogue (OD) approach has been implemented in different countries worldwide. OD not only depends on therapeutic principles but also requires a distinct set of structural changes that may impede its full implementation. In Germany, OD is currently practiced in different mental health care settings across the country. Yet, full implementation of OD principles is limited due to the extreme structural and financial fragmentation of the German mental health care system. With this as a background, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Research focusing on the implementation obstacles has been very scarce for many years, with one study describing organizational challenges observed among the nursing staff in Finland (Haarakangas et al, 2007) and a case study reporting the difficulties of an outreach team practising OD in Denmark (Søndergaard, 2009). More recent research (Gordon et al, 2016;Heumann et al, 2023;Skourteli et al, 2023) highlighted organizational and ideological barriers such as lack of time and resources, rigid professional hierarchy and the burden of working across two different models at the same time (Dawson et al, 2021;von Peter et al, 2023). Although these qualitative studies suggest some adaptation strategies, more global and quantitative research on the implementation of the OD approach is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Research focusing on the implementation obstacles has been very scarce for many years, with one study describing organizational challenges observed among the nursing staff in Finland (Haarakangas et al, 2007) and a case study reporting the difficulties of an outreach team practising OD in Denmark (Søndergaard, 2009). More recent research (Gordon et al, 2016;Heumann et al, 2023;Skourteli et al, 2023) highlighted organizational and ideological barriers such as lack of time and resources, rigid professional hierarchy and the burden of working across two different models at the same time (Dawson et al, 2021;von Peter et al, 2023). Although these qualitative studies suggest some adaptation strategies, more global and quantitative research on the implementation of the OD approach is still needed.…”
Section: Introductionmentioning
confidence: 99%